Lokakarya Penguatan Kolaborasi Antar Lembaga Pelayanan Pendampingan Untuk UMKM di Indonesia - Zainal Abidin (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta (BPJP - STEI), 2021)
The Community Service activity entitled Workshop on Strengthening Collaborative Assistance for MSMEs (Micro, Small and Medium Enterprises) aims to (1) introduce business assistance providers as potential partners in MSME development efforts, (2) identify and explore the advantages and challenges of building partnerships with business mentoring providers, and (3) discuss efforts or the government's collaboration scheme with business assistance provider institutions. The method of community service is through lectures from several competent speakers, followed by interactive discussions using the Zoom application. This event was attended by 250 participants consisting of stakeholders involved in the integrated management of MSMEs and economic empowerment, including Regional Governments, Business Assistance/Incubation Institutions, and Development Partners. The expected result from implementing this community service is an increase in the capacity and condition of MSMEs in efforts to close the knowledge gap through assistance and business services, including through the business incubation program